Tax Policy In The World Of Sport Exemples In Turkey, Uk, Spanish, Italy And Germany : 10.62591/ajpa.2023.12.07 - Ozcan, Busra (Arena-Journal of Physical Activities, 2024)
Taxes are the most important source of revenue the state relies on to maintain public services. The basic objective of our tax system is to collect taxes in a fair and balanced manner, within the framework of the principles set out in the Constitution. Taxes on income make up a large proportion of tax revenues. In this context, salary income is taxed under the Income Tax Act and there are special regulations for the salary of athletes for the promotion of sport. Looking at Turkey’s tax system, different methods of taxing athlete fees have been applied at different times. Comparisons with other countries show that in Turkey, the income tax rates applied to athlete salaries are relatively low, causing problems in terms of tax fairness. The study examined the legal regulations on the taxation of athlete fees and the implementation processes of these regulations, as well as proposals for the correction of practices that distort tax fairness.